Scholarship Practices in Teacher Training Schools in the Ottoman Modernization Period - Kerim Sarıçelik (Tarih Dergisi)
In order to train qualified teachers within the context of educational modernization, teacher training schools were established in Istanbul since 1848 and in the provinces after 1875. In order to increase the appeal of these schools and direct talented and equipped youth towards a service area urgently needed by the state, scholarships were provided to school students under the name of wage. Scholarship procedures implemented in Istanbul and the provinces may vary. The significance of the allocated scholarships in enabling poor but successful youth to receive higher education should be emphasized. This research aims to present the scholarship practice, which has become a tradition in Darülmuallimin (Teacher Training School for Boys) and Darülmuallimat (Teacher Training School for Girls), in all its aspects. Whether the expected benefits of the scholarship program have been realized or not has been questioned in the light of Ottoman archival documents.